The Influence of Workplace-Integrated Exercise Snacks on Cognitive Performance in Sedentary Middle-Aged Adults—A Randomized Pilot Study - Jonas P. Mues; Stefan Flohr; Nicolas Kurpiers (Sports, 2025)
Sedentary behavior is increasingly recognized as a risk factor for various health issues, including cognitive decline. Objectives: This pilot study examined the acute and chronic effects of workplace-integrated exercise snacks—short, vigorous bouts of exercise—on cognitive performance in middle-aged adults. Methods: Twenty-five sedentary but healthy office workers (51.4 ± 5.3 years; 6 m/19 f) participated. The intervention group (n = 12) performed three 1 min bouts of vigorous exercise (running on the spot) daily, four days a week, for four weeks, while the control group (n = 13) maintained their usual routine. Cognitive performance was assessed pre-intervention, shortly following the first exercise bout (acute effects), and post-intervention (chronic effects) using the Trail Making Test and the Stroop Color–Word Test. Results: Significant acute improvements (p ≤ 0.05) were observed across all cognitive outcomes following a single bout of exercise. Significant interaction effects (p ≤ 0.05) were found across all cognitive outcomes after four weeks, indicating sustained cognitive benefits. Conclusion: These findings suggest that workplace-integrated brief, vigorous exercise may lead to both immediate and sustained enhancement in executive functions such as working memory, processing speed, and inhibitory control. They highlight the potential cognitive health benefits of incorporating exercise snacks into sedentary workplace environments.